SOCIO-CULTURAL AND SOCIAL-ECONOMIC ANALYSIS OF PARENTS AND THEIR INFLUENCE ON LEARNING OUTCOMES OF CLASS VII STUDENTS OF SMP NEGERI 11 TANJUNGBALAI SCHOOL YEAR 2020/2021 - Siti Fikriyah Bungsu Arief; Ichwan Azhari; Nasriah Nasriah (Teunuleh Publisher, 2021)
Many factors can affect a student's success in learning, both internal and external factors, such as socio-cultural and economic parents of students. The study aims to analyze the socio-cultural conditions (family environment) and socio-economic conditions of parents (education, employment and parental income) and their effect on students' social study learning outcomes. From most of the socio-cultural conditions of students (family environments) are categorized well. The socio-cultural conditions of students have a significant effect on the learning outcomes of students' social studies with a value of p = 0.004, in socio-economic conditions of the student's parents, most of whom have a low education, work as non-civil servants and the majority of the student's parents' income is relatively low. The education of the student's parents has a significant effect on the student's social studies learning outcomes. The work of the student's parents had a significant effect on the student's social study learning outcomes with a score of p = 0.016. The income of the parents of students had a significant effect on the learning outcomes of social studies of students with a value of p = 0.017, the results of a double logistic regression analysis concluded that the socio-cultural and educational conditions of parents were simultaneously a significant and dominant (strong) influence on social study learning outcomes for students of class VII of Tanjungbalai State Junior High School 11 Tanjungbalai school year 2020/2021.